Emerging investigator series: effect-based characterization of mixtures of environmental pollutants in diverse sediments. Issue 12 (22nd October 2018) - Jahnke, Annika; Sobek, Anna; Bergmann, Melanie; Bräunig, Jennifer; Landmann, Madlen; Schäfer, Sabine; Escher, Beate I.
Abstract : Our study distinguishes the total vs. the bioavailable contamination of mixtures of environmental pollutants in sediments from contaminated sites in Europe and more remote locations in Australia and the Arctic. Abstract : This study investigated whether cell-based bioassays were suitable to characterize profiles of mixture effects of hydrophobic pollutants in multiple sediments covering remote Arctic and tropical sites to highly populated sites in Europe and Australia. The total contamination was determined after total solvent extraction and the bioavailable contamination after silicone-based passive equilibrium sampling. In addition to cytotoxicity, we observed specific responses in cell-based reporter gene bioassays: activation of metabolic enzymes (arylhydrocarbon receptor: AhR, peroxisome proliferator activated receptor gamma: PPARγ) and adaptive stress responses (oxidative stress response: AREc32). No mixture effects were found for effects on the estrogen, androgen, progesterone and glucocorticoid receptors, or they were masked by cytotoxicity. The bioanalytical equivalent concentrations (BEQ) spanned several orders of magnitude for each bioassay. The bioavailable BEQs (passive equilibrium sampling) typically were 10–100 times and up to 420 times lower than the total BEQ (solvent extraction) for the AhR and AREc32 assays, indicating that the readily desorbing fraction of the bioactive chemicals was substantially lower than the fraction bound strongly to the sediment sorptive phases. Contrarily, the bioavailable BEQ in the PPARγ assay was within a factor of five of the total BEQ. We identified several hotspots of contamination in Europe and established background contamination levels in the Arctic and Australia.